Analysis of Mathematical Reasoning Ability of Class XI Students at Bina Husada Mandiri Bekasi Vocational School on Sequences and Series Material - Basuki, Kasih Haryo; Ahsanty, Putri (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to analyze students' mathematical reasoning abilities on sequence and series material. This research was conducted on class XI students of Bina Husada Mandiri Vocational School. This research is descriptive qualitative research. The research subjects taken were 30 class XI students using data collection techniques using purposive sampling. The research results showed that students with low ability were 26.67% with 8 students and those with medium ability were 53.33% with 16 students. Meanwhile, students with high abilities were recorded at 20% with a total of 6 students. Thus, in the sequence and series material, class XI students at Bina Husada Mandiri Vocational School have mathematical reasoning abilities in the medium category. Mathematical reasoning abilities can be developed and improved with support and appropriate learning approaches. With a holistic and focused approach, students can better internalize mathematical concepts and obtain optimal mathematical reasoning skills, thereby increasing the effectiveness of learning on sequence and series material